Analisis Penyebab Pemilih Tidak Menggunakan Hak Suara pada Pilkada Gubernur Sumatera Utara 2024 di Kelurahan Pandau Hulu II Kecamatan Medan Area - Grace Mercy Epsilon Hia; Rina Panggaeban Fransiskus marbun; Zauzza Zahra Stabitah; Bintang P.S.M Purba; Sahala Fransiskus Marbun (PT. Pustaka Cendekia Publisher, 2025)
Regional head elections are a democratic process that allows people to determine their leaders. However, in the 2024 North Sumatra Gubernatorial Election, many voters in Pandau Hulu II Village, Medan Area District, did not use their voting rights. This study aims to analyze the main reasons why voters did not vote in the election. The research method used was descriptive qualitative with interview techniques for 33 respondents from 11 polling stations in Pandau Hulu II Village. The results of the study showed that there were two main factors that caused voters not to use their voting rights. First, demographic factors, where the majority of the population is of Chinese ethnicity who are less interested in regional head elections and tend not to follow the political process. Second, environmental factors, especially heavy rain that occurred since the morning on voting day, which prevented voters from coming to the polling stations. This study provides insight into the factors that influence voters' decisions not to vote and can be used as consideration for election organizers in increasing political awareness and anticipating technical obstacles in the upcoming election.